Provocative F Wave in the Diagnosis of Nonspecific Neurogenic-Type Thoracic Outlet Syndrome - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2012)
Ozgonenel L, Akyuz G, Ozgonenel B, Adatepe T: Provocative F wave in the diagnosis of nonspecific neurogenic-type thoracic outlet syndrome. Am J Phys Med Rehabil 2012; 91: 316-320. Objective: Thoracic outlet syndrome (TOS) is defined as a constellation of clinical symptoms caused by the entrapment of neurovascular structures (subclavian vessels and the brachial plexus) en route to the upper limb via the superior thoracic outlet. Nonspecific neurogenic TOS is not easy to diagnose because there is no investigational technique that has proven to be the diagnostic gold standard. Design: In this study, our aim was to investigate the role of provocative F response in the diagnosis of nonspecific neurogenic TOS. F wave analysis of median and ulnar nerves in neutral and provocative maneuvers was carried out in 21 patients with a clinical diagnosis of nonspecific neurogenic TOS and in 15 healthy volunteers. Results: All findings were within reference range in both groups, and no statistical difference was noted among subject groups, with or without provocative maneuvers. Conclusions: We conclude that the nonspecific neurogenic TOS is a temporary compression process that does not result in a structural damage on the nerve; therefore, significant electrophysiologic changes are not elicited.
Keywords: Electrophysiology; F Wave; Provocative Maneuvers; Thoracic Outlet Syndrome; SOMATOSENSORY-EVOKED-POTENTIALS; COMPRESSION